2014
DOI: 10.1172/jci71858
|View full text |Cite
|
Sign up to set email alerts
|

Platelet factor 4 limits Th17 differentiation and cardiac allograft rejection

Abstract: Th cells are the major effector cells in transplant rejection and can be divided into Th1, Th2, Th17, and Treg subsets. Th differentiation is controlled by transcription factor expression, which is driven by positive and negative cytokine and chemokine stimuli at the time of T cell activation. Here we discovered that chemokine platelet factor 4 (PF4) is a negative regulator of Th17 differentiation. PF4-deficient and platelet-deficient mice had exaggerated immune responses to cardiac transplantation, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 70 publications
2
91
0
Order By: Relevance
“…Histological examination of rejected grafts from Pf4 -/-mice revealed an atypical vasculopathy, with perivascular aggregates composed of T cells and dense infiltrates of neutrophils. Similar neutrophil recruitment after transplantation has been previously observed in Tbx21 -/-mice, also had an increased propensity for Th17 responses after transplantation (8). Recent studies in patients with autoimmune conditions associated with reduced numbers of platelets (and, presumably, PF4) also exhibit increased Th17 cell frequencies (13,14).…”
Section: Loss Of Pf4 Accelerates Graft Rejection By Enhancing Th17supporting
confidence: 73%
See 2 more Smart Citations
“…Histological examination of rejected grafts from Pf4 -/-mice revealed an atypical vasculopathy, with perivascular aggregates composed of T cells and dense infiltrates of neutrophils. Similar neutrophil recruitment after transplantation has been previously observed in Tbx21 -/-mice, also had an increased propensity for Th17 responses after transplantation (8). Recent studies in patients with autoimmune conditions associated with reduced numbers of platelets (and, presumably, PF4) also exhibit increased Th17 cell frequencies (13,14).…”
Section: Loss Of Pf4 Accelerates Graft Rejection By Enhancing Th17supporting
confidence: 73%
“…In this murine model of cardiac transplant, graft rejection is usually mediated by classical Th1-type responses, where CD4 + T cell effectors produce cytokines such as IFN-γ, IL-2, and GM-CSF (9). Although Th1 differentiation was disabled in Pf4 -/-hosts, Morrell and colleagues surprisingly found that grafts in these mice were rejected at an earlier time point compared with control animals (8). Histological examination of rejected grafts from Pf4 -/-mice revealed an atypical vasculopathy, with perivascular aggregates composed of T cells and dense infiltrates of neutrophils.…”
Section: Loss Of Pf4 Accelerates Graft Rejection By Enhancing Th17mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they interact with activated endothelium, undergo chemotaxis,"prime" leukocytes for efficient tissue recruitment, activate other inflammatory cells, exert phagocytosis, release biologically active substances, including adhesive proteins, vasoactive and proinflammatory mediators (1)(2)(3)(4)(5). Major platelet-derived chemokines and cytokines include PF4/CXCL4, pro-platelet basic protein (ppbp), RANTES, inorganic polyphosphate and IL-1β, among a large number of inflammatory molecules (6)(7)(8). Platelet-derived microparticles also contribute to the inflammatory process (9,10).…”
Section: Schlüsselwörtermentioning
confidence: 99%
“…34 On the other hand, PF4 was found to be a negative regulator of Th17 differentiation, thereby limiting cardiac allograft rejection in a murine cardiac transplant model. 35 Platelets also release microparticles, which are small extracellular vesicles (the majority are ;200 nm in diameter) produced via blebbing and fission of the plasma membrane. Although several cells can produce microparticles, platelets appear to be highly effective in their production compared with other cell types.…”
mentioning
confidence: 99%